39 Experience of racial prejudice or discrimination in palliative care settings – a survey of UK specialist palliative care services. (30th January 2023) - Hussain, JA; Hanchanale, S; Lee, J; Khan, N; Abbas, Q; Gupta, G
Abstract : Introduction: Racism is an underlying cause of inequity in health. Little is known about whether and how racism is experienced within specialist palliative care services. Aims: To explore whether and how racial prejudice or discrimination is experienced in specialist palliative care settings. Methods: An online survey was designed and disseminated by the Association of Palliative Medicine Race Equity Committee with external peer review and ethics committee review. Results: To date there have been 769 responses (closing date:31/10/2022) from individuals working across a range of roles and service types. 66% of respondents selected they were White British (dominant ethnicity). 42% of all respondents had witnessed or experienced racism in their palliative care role¬. 19% of respondents had personally experienced racism. Racism witnessed towards patients/visitors was mostly from other staff members. For over half of the respondents who had experienced/witnessed racism, these incidents had occurred within the last year. 44% did not report the racist incidents and the reason for over half of these was because they did not feel comfortable doing so or did not think it would be acted on. 45% of respondents felt their organisation or team represented the diversity of the community it served, but only 35% felt the senior leaders or managers were representative of the community. 49% thought minority ethnic staff were equally likely to be appointed to senior positions-this was more likely if the respondent was white. Qualitative findings expose the different forms and degrees of inter-personal and structural racism experienced. Conclusions: This survey found evidence of interpersonal and structural racial prejudice and discrimination in UK palliative care settings. Impact: Palliative care services must acknowledge that racism can and does occur within their organisations. Work to address this must be prioritised.